Organizational culture and business associativity of micro-enterprises in the textile clothing sector of the Tacna district, 2012 period. - Loza Ticona, Renzi Marilu (2014)
Objective: To determine the relationship between organizational culture and business associations of micro textile garment district of Tacna sector 2012 period. Method: The research is for the basic type, because it has the purpose of obtaining and gathering information in order to build a knowledge base to be added to the existing background information. Result: Were analyzed and interpreted the data processed through quantitative, qualitative analysis, and synthesis, determining the relationship between organizational culture and business association of microenterprises in the textile manufacturing industry Tacna District, 2012 period. Conclusions: There is significant relationship between organizational culture and business association of microenterprises in the textile manufacturing industry Tacna District, 2012 period. The organizational culture present micro Textile Garments Sector Tacna district is inadequate. There is significant relationship between low organizational culture and business association of microenterprises in the textile manufacturing industry Tacna District, 2012 period. Finally, business associations presenting micro Textile Garments Sector Tacn a district is poor, 2012.